2007
DOI: 10.3390/12040907
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Three-dimensional Structure of Gynoside A in Solution using NMR and Molecular Modeling

Abstract: Abstract:The three-dimensional structure of Gynoside A, an ocotillone-type triterpenoid glycoside isolated from Gynostemma pentaphyllum, was determined in pyridine-d 5 and DMSO-d 6 solution through constrained molecular modeling using constraints derived from proton NMR spectra. The calculation yielded well-defined global minima. Except for some quantitative details the overall structure of Gynoside A in pyridine-d 5 shared many common features with that in DMSO-d 6 . The structure in pyridine-d 5 had lower en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Nevertheless only pseudoginsenoside-RT 5 was found in the leaves of Panax ginseng C. A. Mey so far [1] . In addition, there are ocotillol type saponins in the Cucurbitaceae, Martyniaceae and Betulaceae species [2][3][4][5] . The results of the previous researches on pharmacological and biological activities indicated that ocotillol type saponin possessed myocardial protection effect, antibacterial activity, enhancing neuronal activity and anti-tumor promoting activity [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless only pseudoginsenoside-RT 5 was found in the leaves of Panax ginseng C. A. Mey so far [1] . In addition, there are ocotillol type saponins in the Cucurbitaceae, Martyniaceae and Betulaceae species [2][3][4][5] . The results of the previous researches on pharmacological and biological activities indicated that ocotillol type saponin possessed myocardial protection effect, antibacterial activity, enhancing neuronal activity and anti-tumor promoting activity [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Their characteristic triterpenoid aglycone consists of either a 20­( S )-protopanaxadiol (PPD) or 20­( S )-protopanaxatriol (PPT) featuring a hydroxyisopropyl-tetrahydrofuran side chain at the C-20. Naturally, they mainly occur in Panax species (Araliaceae family), but some have also been isolated from Neoalsomitra integrifoliola vine and Gynostemma pentaphyllum herb (Cucurbitaceae family). , Thus, far, less than 20 naturally occurring ocotillol-type ginsenosides have been characterized and reported, namely majonoside R1, R2, pseudoginsenoside F11 (24- R / S epimers), RT2, RT4, RT5, vina-ginsenoside R1 (24- R / S epimers), R2, R5, R6, neoalsoside D1, E1 and gynoside A, B, C. For all these compounds, the C-20 of the sapogenin aglycone has a S -configuration and the sugar units which are d -glucose, l -rhamnose and d -xylose are attached onto the aglycone either at the 3β-OH (PPD) or 6α-OH (PPT). Recently, the 20­( R )-epimer of 24­( R )-pseudoginsenoside F11 was isolated from red American ginseng and novel structures will probably continue to be reported with the aid of modern and more sensitive characterization techniques …”
Section: Introductionmentioning
confidence: 99%
“…1), a lupane-type pentacyclic triterpenoid saponin, could cause vasorelaxation, a property unknown before. Anemoside A 3 was first isolated by our group from the roots of Pulsatilla chinensis (Ranunculaceae) which is commonly used to treat amoebic diseases, vaginal trichromoniasis, and bacterial infections in traditional Chinese medicine [6,7]. We showed previously that anemoside A 3 protected against apoptotic death of PC12 cells caused by sodium cyanide or glucose deprivation [8].…”
mentioning
confidence: 99%